2015
DOI: 10.1136/bmjopen-2014-007356
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study on upright heart rate and BP changing characteristics: basic data for establishing diagnosis of postural orthostatic tachycardia syndrome and orthostatic hypertension

Abstract: ObjectiveWe aimed to determine upright heart rate and blood pressure (BP) changes to suggest diagnostic criteria for postural orthostatic tachycardia syndrome (POTS) and orthostatic hypertension (OHT) in Chinese children.MethodsIn this cross-sectional study, 1449 children and adolescents aged 6–18 years were randomly recruited from two cities in China, Kaifeng in Henan province and Anguo in Hebei province. They were divided into two groups: 844 children aged 6–12 years (group I) and 605 adolescents aged 13–18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 32 publications
0
28
0
3
Order By: Relevance
“…Typically patients will certainly have more signs after a stressor or a physical activity, but the precise triggers that cause the beginning of POTS are unidentified. For as much as 75 percent of patients, POTS signs could improve, and even disappear, by age 21 to 25 years (4) . When experiencing apparent postural orthostatic tachycardia disorder, it is very important to assess and omit additional causes of orthostatism (17) .…”
Section:  Signs and Symptoms Of Potsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically patients will certainly have more signs after a stressor or a physical activity, but the precise triggers that cause the beginning of POTS are unidentified. For as much as 75 percent of patients, POTS signs could improve, and even disappear, by age 21 to 25 years (4) . When experiencing apparent postural orthostatic tachycardia disorder, it is very important to assess and omit additional causes of orthostatism (17) .…”
Section:  Signs and Symptoms Of Potsmentioning
confidence: 99%
“…Therefore, the orthostatic HR requirement for the medical diagnosis of adult POTS might not be appropriate for children and adolescents and need to be reviewed. Singer et al (4) recommended that it appertained to use the requirements that the orthostatic HR increment ≥ 40 beats/min or absolute orthostatic HR ≥ 130 beats/min (for ages 13 years and younger), or ≥ 120 beats/min (for ages 14 years and older) within 5 min of head-up tilt, along with the symptoms of orthostatic intolerance for pediatric POTS. In a cross-sectional study, consisting of 1449 children and adolescents aged 6-18 years, Zhao et al (5) suggested that POTS need to be suggested in kids and adolescents when the orthostatic HR increment ≥ 40 beats/min, or absolute orthostatic HR ≥ 130 beats/min (for ages 12 years and younger), or ≥ 125 beats/min (for ages 13 years and older) within 10 min relocating from supine to upright setting.…”
Section: Introductionmentioning
confidence: 99%
“…While, patients with unexplained syncope need head-up tilt test (HUTT) or follow-up [12][13][14][15]. The HUTT can help in the diagnosis of VVS and its hemodynamic types, vasoinhibitory type (VI), cardioinhibitory type (CI) and mixed type (M) [17,18], POTS [18][19][20][21][22], OH [21], or OHT [22] (IIa; A).…”
Section: Classes Underlying Diseasesmentioning
confidence: 99%
“…In the standing test, first, the child lays supine for around 10-30 min for heart rate (HR), BP and ECG recordings. Then, the child is advised to stand for another 10 min, with simultaneous monitoring of HR, BP and ECG [20,22] (IIa; A). [22], OH [23] or OHT [22,24].…”
Section: Standing Testmentioning
confidence: 99%
“…Its symptoms had significant associations with postural change. Main hemodynamic characteristics of POTS was a significant increase in heart rate at upright position compared with supine position, and the increase amplitude of heart rate is ≥40 heart beats/min, or the maximum heart rate is ≥120 heart beats/min [1]. Main clinical features are orthostatic intolerance symptoms, such as dizziness, amaurosis, chest tightness, pale complexion, blurred vision, long out-gassing and palpitation, and some children patients might even have syncope, seriously affecting daily life and academic records of children patients [23].…”
Section: Introductionmentioning
confidence: 99%